Analysis Of The Influence Of Lifestyle And Halal Labeling On Purchasing Decisions For Cosmetic Products In Pagar Jati Village, Central Bengkulu - Handayani, Metri; Asnaini, Asnaini; Hartini, Kustin (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: The purpose of this study was to analyze and understand the effect of lifestyle and price on purchasing decisions for halal-labeled products, specifically among women in Pagar Jati Village, Central Bengkulu. Methodology: This study used a descriptive research design with a quantitative approach. A nonprobability sampling technique with saturated sampling was applied, selecting 82 respondents for the survey. Results: The results revealed that the lifestyle variable (X1) significantly influences purchasing decisions for cosmetic products, with a regression coefficient of 5.757 and a probability value of 0.0000, which is smaller than the significance level α = 0.05. The halal label variable (X2) also has a significant effect, with a regression coefficient of 2.522 and a probability value of 0.0137. Additionally, both variables together positively influence purchasing decisions, with a regression value of 31.830 and a probability value of 0.000. Findings: Lifestyle and halal label variables account for 43.2% of the influence on purchasing decisions for cosmetic products, with the remaining 56.8% being influenced by other factors not examined in this study. Novelty: This research provides new insights into the role of lifestyle and halal labeling in purchasing decisions within a specific demographic in Central Bengkulu. Originality: The study focuses on halal-labeled products, an area of growing interest in consumer behavior studies, particularly in the context of women in rural areas. Conclusions: Lifestyle and halal labeling significantly influence cosmetic product purchasing decisions, highlighting the importance of these factors in marketing strategies. Type of Paper: Empirical research paper.